Do In Utero Events Contribute to Current Health Disparities in Reproductive Medicine? - Sauerbrun-Cutler, May-Tal; Segars, James H. (Seminars in Reproductive Medicine, 2013)
Health disparities exist in reproductive medicine as discussed in detail in the subsequent articles of this issue; however, in most cases, the exact cause of these differences is unknown. Some of these disparities can be linked to environmental exposures such as alcohol and other hazardous toxic exposures (polycarbonate, pesticides, nicotine) in adults. In addition, low socioeconomic status, behavioral risk factors, and lack of education have been linked to poor obstetric and reproductive outcomes in minority groups. Aside from these various environmental exposures later in life, there is evidence that adverse events in utero could contribute to poor reproductive outcome in specific minority groups. We will focus on the developmental origins of health and disease as a possible causal mechanism for health disparities in reproductive diseases, as this perspective may suggest tractable solutions of how to address and eliminate these health disparities.
Keywords: DOHaD; preterm labor; obesity; African Americans; preterm birth